Design of Product Characteristics 3D Model Display System Based on Digital Earth - Li, Xiangzhen; Xia, Yanqing; Yin, Hongcheng; Zhang, Yang; Liu, Shuai; Wu, Xichen; Xie, Xiaodan (2023 8th International Conference on Image, Vision and Computing (ICIVC), 2023)
The data visualization of traditional two-dimensional GIS maps cannot satisfy the display of the target model and lacks the feeling from three-dimensional space, so it is impossible to map the details of the target. This system adopts B/S architecture for development, builds digital Earth on the Web side, encapsulates ZGIS, an open-source JavaScript framework that creates 3D virtual earth and 2D plane map in the Web browser. At the bottom, WebGL is used as the graphics rendering engine, and encapsulates the underlying WebGL interface. It can perform hardware acceleration for rendering 3D models of product features on the browser side, and smoothly draw 3D scenes and models of product features on the graphics card, which greatly improves the performance of 3D visualization on the Web side and improves user interaction experience.